Hitting Back: Women's Use of Physical Violence Against Violent Male Partners, in the Context of a Violent Episode. (October 2015) - Fanslow, Janet L.; Gulliver, Pauline; Dixon, Robyn; Ayallo, Irene
This article explores women's use of physical violence in the context of experiencing intimate partner violence (IPV). Data were drawn from the New Zealand Violence Against Women Study, a cross-sectional household survey conducted using a population-based cluster-sampling scheme. Multinomial logistic regression was used to identify factors associated with women's use of physical violence against their partners when they were being physically hurt. Of the 843 women who had experienced physical violence perpetrated by an intimate partner, 64% reported fighting back at least once or twice whereas 36% never fought back. Analyses showed that women's use of violence more than once or twice was associated with experience of severe IPV, IPV that had "a lot of effect" on their mental health, and with children being present when the woman was being physically abused. Women's use of physical violence only once or twice was associated with both partners having alcohol problems and both having been exposed to violence as a child. Of the women who fought back, 66% reported that this did not result in the violence stopping.